THE CHALLENGES AND SOLUTIONS FACED BY ALL ENGLISH TEACHERS IN TEACHING INCLUSIVE SHILDREN IN BENGKULU CITY STATE ELEMENTARY SCHOOLS - Yeyen Rahmadiana (Berajah Journal, 2022)
The focus of this research is to find out what are the challenges faced by English teachers at SD 03 Bengkulu and SD Alam Ahlia Bengkulu and how to overcome them, starting from learning activities, as well as facilities and infrastructure for English teachers and inclusive children. research results (1) educators, especially English teachers receive inclusive education training (2) classroom management is adapted to inclusive children (3) annually receive 2 inclusive children (4) use an accommodating curriculum (5) supporting factors: parental care, shadow teachers and government, inhibiting factors: uncaring parents and unclear regulations